2006
DOI: 10.1128/aem.72.2.1079-1085.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pure-Culture Growth of Fermentative Bacteria, Facilitated by H 2 Removal: Bioenergetics and H 2 Production

Abstract: We used an H 2 -purging culture vessel to replace an H 2 -consuming syntrophic partner, allowing the growth of pure cultures of Syntrophothermus lipocalidus on butyrate and Aminobacterium colombiense on alanine. By decoupling the syntrophic association, it was possible to manipulate and monitor the single organism's growth environment and determine the change in Gibbs free energy yield (⌬G) in response to changes in the concentrations of reactants and products, the purging rate, and the temperature. In each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…More recent experiments demonstrate that fermentative bacteria similarly adjust their hydrogen production rates to maintain constant Gibbs energy yields despite experimental changes in reactant concentrations, product concentrations, and temperature (Adams et al, 2006), while Jin and Bethke (2003) have showed how rates of reaction may be directly dependent on the net Gibbs energy of respiration reactions combined with ATP synthesis.…”
Section: Maintenance Of a Complex Ecosystem By Feedbacks Between Micrmentioning
confidence: 98%
“…More recent experiments demonstrate that fermentative bacteria similarly adjust their hydrogen production rates to maintain constant Gibbs energy yields despite experimental changes in reactant concentrations, product concentrations, and temperature (Adams et al, 2006), while Jin and Bethke (2003) have showed how rates of reaction may be directly dependent on the net Gibbs energy of respiration reactions combined with ATP synthesis.…”
Section: Maintenance Of a Complex Ecosystem By Feedbacks Between Micrmentioning
confidence: 98%
“…However, little is known about the molecular mechanisms involved in the formation and maintenance of these catalytic units. Even under optimal growth conditions, free energy changes are close to equilibrium (12)(13)(14) and the available free energy must be shared by the different organisms (4). Truly, syntrophy represents an extreme existence, that of a marginal energy economy.…”
mentioning
confidence: 99%
“…[92125] These results demonstrated that actually growing of cells and adenosine triphosphate synthesis. [26] For all batch tests, the mass balance recovery based on the e − eq were closed within 5.2%–13.5% and depicted good detection of end products.…”
Section: Discussionmentioning
confidence: 97%